Beyond acute stroke: Rate of stroke transfers to a tertiary centre following the implementation of a dedicated inpatient teleneurology network. (May 2021) - Al Kasab, Sami; Almallouhi, Eyad; Debenham, Ellen; Turner, Nancy; Simpson, Kit N; Holmstedt, Christine A
Introduction: This study evaluated the impact of establishing an inpatient teleneurology consultation service alongside an already established telestroke network on the stroke transfers to the hub. The study also aimed to assess the financial impact of establishing this network. Methods: Prospectively collected data on all stroke patients evaluated through our telestroke and teleneurology networks between January 2008 and March 2018 were interrogated. For all spokes (eight sites) that had both teleneurology and telestroke services, we compared the rate of transfers to the hub before and after the establishment of the teleneurology network in August 2014. The cost reduction was estimated using the Medicare 5% standard analytic files. Results: A total of 4296 stroke patients were evaluated during the study period. Of these, 2493 were seen before and 1803 were seen after the implementation of the teleneurology network at the included sites. Patients in the pre-teleneurology group were older (66.4 years ( SD  = 14.7 years) vs. 67.8 years ( SD  = 15.1 years); p  = 0.002). Otherwise, there were no differences in baseline characteristics. Patients in the pre-teleneurology group were more likely to be transferred to the telestroke hub (29.4% vs. 20.2%; p  < 0.001). The estimated mean cost reduction for each one minus the cost of transfer was estimated to be US$4997. Discussion: The implementation of an inpatient teleneurology network was associated with a significant reduction in the transfer rate of stroke patients to hospitals with a higher level of care and could lead to a significant cost reduction.